Ovarian follicular dynamics during the interovulatory interval in Gaddi goats - SHARMA, AMIT; SOOD, PANKAJ; DOGRA, PRADEEP (The Indian Journal of Animal Sciences, 2018)
Goat husbandry is an important component of the agrarian society of Himachal Pradesh, India. Adult, healthy, non-pregnant, Gaddi does (7), aged 4.52±0.39 years, weighing 27.07±1.03 kg were investigated during breeding season (January–February 2017) at University Farm for follicular wave characterstics. Cyclic Gaddi goats during breeding season mainly manifested four wave pattern of follicular growth (5; 71.4%), while the remaining animals had either 3 or 5 wave pattern (1 each; 14.3%). The last wave in all these animals was ovulatory, with interovulatory and interoestrus interval of 20.85±0.63 and 21.0±0.53 days, respectively. Average (Mean±SEM) diameter of ovulatory follicle was 6.85±0.24 mm. The average progesterone concentration peaked to 11.89±1.55 ng/ml at day 14 of estrus cycle. Mean luteal and follicular phase durations were 17.57±0.36 and 3.14±0.26 days, respectively. Overall daily total number of follicles during the breeding season were 5.50±0.55 which suggests pronounced ovarian activity.